Covid-19 and tuberculosis: the encounter between new threats and old diseases - Suárez Benites, Carolina Marley (2021)
A storm called COVID-19 has been destabilizing the health systems of almost everything the world. In almost 8 months it has gone from being a report of atypical pneumonia with etiology unknown to be the pandemic of the 21st century. In Peru, the first confirmed case was March 6, and until the beginning of July has been claiming the lives of more than 10,000 people.